Suppression of gross chromosomal rearrangements by a new alternative replication factor C complex - Banerjee, Soma (2007)
Defects in DNA replication fidelity lead to genomic instability. Gross chromosomal rearrangement (GCR), a type of genomic instability, is highly enhanced by various initial mutations affecting DNA replication. Frequent observations of GCRs in many cancers strongly argue the importance to maintain high fidelity of DNA replication to suppress carcinogenesis. Recent genome wide screens in Saccharomyces cerevisiae identified a new GCR suppressor gene, ELG1, enhanced level of genome instability gene 1. Its physical interaction with proliferating cell nuclear antigen (PCNA) and complex formation with Rfc2–5p proteins suggest that Elg1 functions to load/unload PCNA onto DNA during a certain DNA metabolism. High level of DNA damage accumulation and enhanced phenotypes with mutations in genes involved in cell cycle checkpoints, homologous recombination (HR), or chromatin assembly in the elg1 strain suggest that Elg1p-Rfc2–5p functions in a fundamental DNA metabolism to suppress genomic instability.